2013
DOI: 10.1038/jp.2013.35
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive cardiac monitoring in pregnancy: impedance cardiography versus echocardiography

Abstract: Objectives The objective of this study was to report thoracic impedance cardiography (ICG) measurements and compare them to echocardiography (echo) measurements throughout pregnancy and in varied maternal positions. Methods A prospective cohort study involving 28 healthy parturients was performed using ICG and echo at three time points and in two maternal positions. Pearson correlations, Bland-Altman plots and paired t-tests were used for statistical analysis. Results Significant agreements between many bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…ICG has been proposed as an alternative device for the assessment of cardiovascular function because it is quick, user‐friendly, operator‐independent, requires minimal training to use and is suitable for bedside functional hemodynamic monitoring . Although its use has been controversial and it is not interchangeable with echocardiography, Burlingame et al demonstrated a significant correlation between ICG and echocardiography during pregnancy. In addition, modest agreement and significant correlation with echocardiography in measuring SV and CO variation after PLR have been demonstrated in singleton pregnancies .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ICG has been proposed as an alternative device for the assessment of cardiovascular function because it is quick, user‐friendly, operator‐independent, requires minimal training to use and is suitable for bedside functional hemodynamic monitoring . Although its use has been controversial and it is not interchangeable with echocardiography, Burlingame et al demonstrated a significant correlation between ICG and echocardiography during pregnancy. In addition, modest agreement and significant correlation with echocardiography in measuring SV and CO variation after PLR have been demonstrated in singleton pregnancies .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study cohort did not consist of a homogeneous ethnic population. The accuracy of measuring hemodynamics using ICG has been questioned, but this technique has been validated in pregnant populations and significantly correlates with echocardiography, also during PLR . Moreover, a new generation of ICG devices and recent updates in the ICG signal analysis software have improved ICG measurement accuracy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given its accessibility and ease of use, impedance cardiography at one time became very attractive for the measurement of CO in both pregnant and non‐pregnant women. Nevertheless, most validation studies, in both non‐pregnant and pregnant women, using any of the available devices, have not been able to show sufficient accuracy and precision as compared with reference methods such as PAC or TTE in reflecting absolute CO values. As such, at the moment, all these devices (Table ) are probably not suited to showing ‘true CO’ values.…”
Section: Methods Of Co Measurementmentioning
confidence: 99%
“…Moreover, it has been used to detect ischemia [12]. Furthermore, it may be useful to examine the effect of different diseases of the autonomic nervous system like the Parkinson's disease [13,14], for monitoring pregnant women [15,16], for diagnosis and treatment of patients with hypertension [17,18]. Likewise, it has been used to monitor surgical operations [19,20] and dialyzed patients [21,22].…”
Section: Introductionmentioning
confidence: 99%